Abortive cell culture infections of nuclear polyhedrosis viruses as model systems for host specificity - Bilimoria, S. L.; Demirbag, Zihni; NG, Harry; Reinisch, Alesia J. (Pesquisa Agropecuaria Brasileira, 1992)
We describe virus growth and cytopathic effect (CPE) in an abortive infection involving Autographa californica nuclear polyhedrosis virus (AcMNPV) and a Bombyx mori line. Our results show that AcMNPV causes complex and very unusual CPE in B. mori cells. This involves the formation of sacs and protrusions in addition to the nuclear hypertrophy and rounding normally observed in productive infections. Infection of B. mori cells with UV-inactivated AcMNPV induces only sacs, indicating that viral gene expression is not required for this effect. No infectious virus is produced in B. mori cells. Electron microscopy show that virogenic stroma, but no virions or polyhedral inclusion bodies, are formed in B. mori cells. Nucleocapsids are detected in 20 percent of the infected cells, but are defective. Our results suggest that a virion component of an NPV causes cytopathic effect. This principle has important implications in the identification of viral genes for engineering transgenic crop plants resistant to pest insects.